2019
DOI: 10.1242/jeb.211730
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon regulation of carbohydrate metabolism in rainbow trout: in vivo glucose fluxes and gene expression

Abstract: Glucagon increases fish glycemia, but how it affects glucose fluxes in vivo has never been characterized. The goal of this study was to test the hypothesis that glucagon stimulates hepatic glucose production (Ra) and inhibits disposal (Rd) of rainbow trout. Changes in the mRNA abundance of key proteins involved in glycolysis, gluconeogenesis, and glycogen breakdown were also monitored. Results show that glucagon increases glycemia (+38%) by causing a temporary mismatch between Ra and Rd before both fluxes conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…In the present study, in vitro incubation with glucagon activated gluconeogenesis and induced glucose production in hepatocytes of the Japanese flounder. In line with the present study, bovine glucagon intraperitoneally injected in blunt snout bream (Megalobrama amblycephala) and infused in rainbow trout increased the hepatic glucose production and the mRNA levels of gluconeogenesis-related genes [36,37]. Earlier studies concerning the glucagon signaling pathway in fish found that bovine glucagon bound GCGR (by measuring the radioactivity of hepatocyte-bound 125 I-labelled glucagon) and increased PKA activity in American eels (Anguilla rostrata) and brown bullheads (Ictalurus nebulosus) hepatocytes [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, in vitro incubation with glucagon activated gluconeogenesis and induced glucose production in hepatocytes of the Japanese flounder. In line with the present study, bovine glucagon intraperitoneally injected in blunt snout bream (Megalobrama amblycephala) and infused in rainbow trout increased the hepatic glucose production and the mRNA levels of gluconeogenesis-related genes [36,37]. Earlier studies concerning the glucagon signaling pathway in fish found that bovine glucagon bound GCGR (by measuring the radioactivity of hepatocyte-bound 125 I-labelled glucagon) and increased PKA activity in American eels (Anguilla rostrata) and brown bullheads (Ictalurus nebulosus) hepatocytes [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…Carbohydrates are important ingredients in the diets of cultivated fish due to supplying energy at low cost and improving physical quality of feed. The endocrine regulatory network of glucose metabolism in fish has not been sufficiently elucidated, although the roles of pancreatic hormones insulin and glucagon in the glucose homeostasis of fish has been extensively explored [28][29][30]. Adiponectin and leptin are two major members of adipokines, which have a profound influence on insulin sensitivity and energy balance in mammals [31].…”
Section: Discussionmentioning
confidence: 99%
“…It diffuses through the cell plasma membrane, binds to the glucocorticoid receptor (GR) and then translocates into the nucleus to induce the expression of gluconeogenic genes (Teles et al, 2013). Binding of other transcriptional regulators to these gene promoters is required to activate their transcription, such as those mediated by the hormone glucagon via a complex series of enzymatic reactions (Forbes et al, 2019). Plasma cortisol levels of fish handled 4 times a week (NET4 group from NET trial), published in another work (Raposo de Magalhães et al, 2020b), were significantly increased when compared with control fish.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%